Lipase-catalyzed asymmetric acylation in the chemoenzymatic synthesis of furan-based alcohols - Hara P; Turcu MC; Sundell R; Tosa M; Paizs C; Irimie FD; Kanerva LT (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
Eight racemic 1-(furan-2-yl)ethanols were prepared from the corresponding carbonyl compounds for enantioselective acylation studies, and seven of them were used in preparative-scale kinetic resolutions with Candida antarctica lipase B (Novozym 435) and vinyl acetate in dried diisopropyl ether. Mechanism-based competition between the (R)-acetate (enzymatic acylation product), vinyl acetate (added acylating reagent), and acetic acid (enzymatic hydrolysis product) toward CAL-B, together with the residual water of the lipase were shown to be potential reasons for side reactions, which affected the course of the kinetic resolution of 1-[5-(2-chlorophenyl) and (4-bromophenyl)furan-2-yl]ethanols. Clear effects were not observed with the other alcoholic substrates. Alcoholysis of the enantiomerically enriched (R)-acetates with methanol and CAL-B in diisopropyl ether was shown to be a potential method for the deprotection of the (R)-acetates and the formation of (R)-alcohols. (C) 2012 Elsevier Ltd. All rights reserved.